EFFECTIVITY OF CAPTOPRIL, LOSARTAN, AND AMLODIPINE ON HYPERTENSION IN RAT MODEL OF GENTAMICIN-INDUCED RENAL FAILURE - Suliska S Farm, Nova
Introduction. The heart and kidneys are two organs that are interrelated, both in physiological and pathological conditions. Abnormalities one organ will affect the function of other organs. Based upon the results of the study, renal failure would lead to hypertension. Conversely, hypertension would also trigger kidney failure.This research aimed to compare the effects of captopril, losartan, and amlodipine for hypertension caused by renal failure. Methods. The rats were divided into 5 groups: negative control, positive control, captopril 120 mg/kg bw, losartan 20 mg/kg bw, and amlodipine 10 mg/kg bw group. All groups were induced by gentamicin 80 mg/kg bw for 5 days except negative control group. Furthermore, the test preparation was given for 2 weeks. Parameters in this test were serum creatinine, blood pressure, organ index, histology, and cardiac collagen. Serum creatinine and systolic blood pressure were measured on time before induction, after induction 5 days , and on day 7 and 14 of therapy. Blood pressure was measured by using a set Kent Scientific's CODA system tools. At the end of the test, kidney and heart were isolated, organ index were counted, and histological preparations were made. Ehrlich Haematoxylin and eosin stain used to stain the kidney. Masson’s trichrome stain used to stain cardiac collagen to color the collagen in the heart. Cardiac histology were observed under a microscope and analyzed using image analyzer ImageJ software to determine the levels of collagen. Result. Serum creatinine was increased in all groups after induction for 5 days. Significant difference (P<0,05) occured in positive control, captopril, losartan, and amlodipine group to negative control group. On the 14th day of therapy, serum creatinine were decreased in all induction group. Renal index positive control, captopril, losartan, and amlodipine group showed significant differences when compared to the negative control group (P<0,05). Profile of renal histology showed cortical damage to the kidneys. Losartan 20 mg/kg bw group could lower systolic blood pressure when compared to the positive control group (P<0,05). Cardiac index losartan group showed significant differences when compared to the positive control group (P<0,05). Profile cardiac histology showed the least amount of collagen tissue formation occurred in the losartan group (4,712%). Conclusion. The best antihypertensive therapy was demonstrated by losartan 20 mg/kg bw group compared to positive control group for hypertension caused by renal failure.